ANALISIS PENGARUH KUALITAS LABA AKUNTANSI TERHADAP SENSITIVITAS ALIRAN KAS INVESTASI - , MEIRISA AMELIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to give empirical evidence about the negative relation between accounting quality as measured by total current accrual and sensitivity cash flow investment on a sample of manufacture companies in Indonesia Stock Exchange. This research also aims to examine the effect of audit firm size and dividend payout ratio as moderate variable on the relation between accounting quality and sensitivity cash flow investment. The sample used in this research is 37 manufacturing firms listed in Indonesia Stock Exchange along 2008-2009, which makes the sample 74. The method of sample selection using purposive sampling method. The criteria from the population of this research is: (1) have complete data required in this research (2) issued financial statement on December 31, 2008 and December 31, 2009. The research proves that there is a negative relation between accounting quality and sensitivity cash flow investment. Moreover, audit firm size is able to moderate the relation between accounting quality and sensitivity cash flow investment on research model 2 which added an element of change in revenue and PPE on accounting quality calcuation.